The role of public relations in shaping the mental image of municipal sector employees in the Eastern Region (The International Journal of Educational Sciences and Arts, 2024)
The study showed that effective public relations activities, including media campaigns and direct communication with employees, contribute significantly to improving the mental image of the municipal sector. These activities play a major role in enhancing employees’ confidence in their management and raising their level of job satisfaction. The study also found that continuous and comprehensive internal communication increases employee satisfaction and enhances their sense of belonging. Public relations contribute to achieving alignment between management goals and employee aspirations, which helps achieve a stable and supportive work environment. The results indicated that transparency in communication processes between management and employees is one of the essential elements for building a positive and reliable relationship. This transparency contributes to reducing rumors and misunderstandings, which increases positive interaction between management and employees and enhances their impressions of the institution. The study also highlighted the effectiveness of modern technical tools in enhancing internal communication, as the use of these tools contributes to facilitating the exchange of information and clarifying procedures, which leads to improving the effectiveness of communication and enhancing the positive mental image of the municipal sector. The study stressed the importance of adopting sustainable public relations strategies aimed at continuous and constructive communication with employees, to support the long-term goals of the sector. She recommended the need to focus public relations efforts on transparency, continuous communication and the use of modern technologies, which contributes to creating a positive work environment and enhances job satisfaction and belonging among employees, thus achieving a positive and supportive mental image of the municipal sector in the Eastern Region.
Keywords: Public Relations; Mental Image; Job Satisfaction; Municipal Sector; Eastern Region